Review: Art and Immanence: a good encounter between Spinozaand Vermeer - Paula, Marcos Ferreira de (Cadernos Espinosanos, 2012)
Review of the book Vermeer and Spinoza: Immanence in philosophy and painting, Sarah Hornak, published in Brazil in 2010 by publisher Paulus.